FAKTOR YANG BERHUBUNGAN DENGAN SKOR POLA PANGAN HARAPAN PADA RUMAH TANGGA SASARAN DI DESA BATUKANDIK, NUSA PENIDA - Dewi, Anak Agung Sagung Putri Kusuma; Utami, Ni Wayan Arya (ARCHIVE OF COMMUNITY HEALTH, 2019)
Expected Food Pattern (EFP) is composition of dietary diversity based on energy contribution on the main food.  It was known that EFP score of Bali Province year 2014 was remaining low (58,2%). Low EFP score was mainly found in poor household and the largest number of poor households in year 2013 were found in di Batukandik village of Nusa Penida Island. This study aimed to describe household EFP score, number of family members, mother’s knowledge about nutrition, family income level, household food expenditure, diet prohibition and land ownership status with EFP score. This quantitative study was conducted with cross sectional design . Samples were 64 poor household which selected by cluster random sampling. Data was analyzed univariate and bivariate using chi square test. Result showed that mother’s knowledge about nutrition (OR= 4,21; 95%CI OR=1,20-15,78; p=0.01), family income level (OR= 10; 95%CI OR= 1,99-63,72; p=0.00) and household food expenditure (OR= 6,28; 95%CI OR= 1,47-37,12, p=0.00) were significantly associated with PPH score. Meanwhile number of family members, diet prohibition land ownership status was not significantly associated with EFP score. Keywords : Expected Food Pattern, nutrition, family income, food expenditure